2018
DOI: 10.1007/s11934-018-0764-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of Minimally Invasive (Micro and Ultra-mini) PCNL for Adult Urinary Stone Disease in the Modern Era: Evidence from a Systematic Review

Abstract: Purpose of ReviewThe role of PCNL and the expertise surrounding it has expanded in recent decades. Miniaturisation of equipment and instrument size has formed a part of this innovation. Although an increasing number of studies have been performed on miniaturised PCNL (Mi-PCNL) recently, a critical appraisal on these is lacking. We therefore conducted a systematic review of the literature to evaluate the efficacy, safety and feasibility of Mi-PCNL techniques (< 15 Fr).Recent FindingsA systematic review was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…Jones et al published a systematic review study investigating the role of MicroPNL and UMP. Across seven studies a total of 262 patients were undergone UMP with a mean of stone size 18.6mm, SFR of 88.3% and complication rate of 6.2% (19). In our study, we calculated the SFR on 3 rd month control.…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al published a systematic review study investigating the role of MicroPNL and UMP. Across seven studies a total of 262 patients were undergone UMP with a mean of stone size 18.6mm, SFR of 88.3% and complication rate of 6.2% (19). In our study, we calculated the SFR on 3 rd month control.…”
Section: Discussionmentioning
confidence: 99%
“…Although our review shows a good SFR for LPS, information on pelvicalyceal anatomy might prove to be useful when treating stones with unfavourable anatomy especially when they are large and have a hard composition. While IW and IL may not be as important, IPA seems to be important (< 30°) and in these cases an alternate treatment option such as minimally invasive PCNL procedure could be considered [28,29]. This is especially important for informed decision making with the patients, when counselling them for the treatment success for LPS and discussing alternate treatment options.…”
Section: Strengths Limitations and Areas Of Future Researchmentioning
confidence: 99%
“…In general, the tract sizes were <15‐Fr (UMP <15‐Fr, micro‐PCNL <10‐Fr) . A recent systematic review concluded that UMP and micro‐PCNL can yield good stone‐free rates with low morbidity, and should be considered when ESWL or RIRS are prone to fail or have failed . In contrast, when mini‐PCNL was shown to have higher stone‐free rate than RIRS, UMP and micro‐PCNL had similar stone‐free rates with RIRS, and therefore mini‐PCNL was recommended for renal stones, as the current evidence has shown …”
Section: Pcnlmentioning
confidence: 99%